2018
DOI: 10.1111/ina.12457
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of environmental factors on human perception and objective performance: A review of experimental laboratory works

Abstract: This study reports the outcomes of a literature survey aimed at exploring how different environmental factors-that is acoustic, thermal, visual, and air quality stimuli-interact in affecting building occupants' perception and performance. Recent laboratory studies have been collected, and their methodological approaches reviewed in terms of experimental design, adopted exposures conditions, perception and performance assessment methods. Results have been summarized and compared to identify interaction patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(91 citation statements)
references
References 74 publications
(434 reference statements)
0
79
1
Order By: Relevance
“…This is not the case in a laboratory environment, since the participants know they will not have to work under these conditions in the future. The hypothesis is supported by (Torresin, 2018) mentioning that participants of a laboratory study might have lower motivation than real office workers, causing them to be more resilient to environmental stress.…”
Section: Expectations Towards a Familiar Environmentmentioning
confidence: 97%
See 2 more Smart Citations
“…This is not the case in a laboratory environment, since the participants know they will not have to work under these conditions in the future. The hypothesis is supported by (Torresin, 2018) mentioning that participants of a laboratory study might have lower motivation than real office workers, causing them to be more resilient to environmental stress.…”
Section: Expectations Towards a Familiar Environmentmentioning
confidence: 97%
“…Several mentions can be found in the literature where it is reported that exposure conditions in laboratory tests of indoor comfort studies are often higher than the ones experienced in most buildings (Torresin, 2018, Lamb, 2016, Chinazzo, 2018. This trend is seen in the field of daylighting as well.…”
Section: Difference In Stimulus Ranges and Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, many studies have been conducted to investigate the impact of indoor environmental factors on human performance, focusing on one factor at a time (Baron et al, 1992;Furnham and Strbac, 2002;Heschong Mahone Group, 2003;Lan and Lian, 2009;Reinten et al, 2017;Valančius and Jurelionis, 2013;Wargocki, 1998). However, building occupants are exposed simultaneously to multiple factors and their performance might depend not only on the presence of individual factors but also on their combination (Torresin et al, 2018). Only few studies exist on the effects of the simultaneous presence of multiple indoor stimuli on objective or subjective performance (Balazova et al, 2007;Hygge and Knez, 2001;Knez and Hygge, 2002;Liebl et al, 2012;Lin, 2014;Löfberg et al, 1975;Veitch, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…The main ecological factors are temperature, humidity, air movement, qualitative and quantitative air microflora composition. These indices depend on many parameters: locality of a building, quality of used construction and finishing materials [1], аs well as stay of people in the building [2]. People often spend 80% -90% of time indoors [4].…”
Section: Introductionmentioning
confidence: 99%